The Potential Use of Crude Glycerin as an Alternative Feed and Its Effect on the Growth of Mutiara Catfish (Clarias gariepinus) - Anggraini, Rr. Citra P. Kusuma; Rochvita, Ana; Priasiwi, Wisnu; Panjaitan, Dennys (Agrikan Jurnal Agribisnis Perikanan, 2023)
Mutiara catfish, the second largest food fish in Magelang Regency, faces challenges due to high feed prices. To address this, researchers are exploring the use of crude glycerin biodiesel waste as an alternative feed. This research aims to determine the potential of crude glycerin as an alternative feed for mutiara catfish and its impact on their growth. The study involved selecting feed raw materials, formulation, manufacturing, feeding, observing fish growth, water quality, and proximate testing of test feed. The research used a randomized design with four treatments and three replications. The test feed consisted of P1 25% crude glycerin, P2 50% crude glycerin, P3 75% crude glycerin, and PK, a control in the form of pellets. Feeding was carried out twice a day using the ad satiation method. The study found that the P1 25% crude glycerin feed had the second-best results regarding 19 grams weight gain, 67.85% specific growth rate, 8 cm length growth, and 0.05 feed conversion ratio. The feed also had a 100% survival rate. The water quality was measured, with temperature and pH values ranging between 25-30â„ƒ and 6.98-7.63. The proximate test results showed that the P1 feed had the second-best 12.70% water content, 20.51% ash content, 1.47% fat content, 15.04% protein content, and 50.28% carbohydrate content. The study concluded that the test feed effectively influences fish growth, but further research is needed to optimize feed nutrition.